2013
DOI: 10.1002/jgrd.50293
|View full text |Cite
|
Sign up to set email alerts
|

Ozone distribution in the lower troposphere over complex terrain in Central Chile

Abstract: [1] Observations were performed in 12 communities of Central Chile in order to determine the horizontal gradients of ozone in the Santiago Basin and surrounding valleys. Higher ozone mixing ratios were found northeast of the Santiago Basin and included east of the Aconcagua Valley (~70 km from Santiago) suggesting that photochemical pollution produced in Santiago is capable of passing through the Chacabuco mountain chain (~1.3 km) and have impact downwind from the regions with the largest NO x and VOC emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…Factors such as the existence of internally mixed aerosols (e.g., Jacobson, 2001), non-spherical particles (e.g., Wang et al, 2013) or the presence of upper aerosol layers or residual layers (e.g., Seguel et al, 2013) might help explain model underestimation with respect to observations. The study by Seguel et al (2013) showed near surface ozone origin measured in the residual layer by ozonesondes that accumulates between the top of the mixed layer and the base of the subsidence inversion. Additionally, data from an elastic Light Detection and Ranging system, and a ceilometer over Santiago show unequivocal layers of aerosols above the mixed boundary layer (Muñoz and Alcafuz, 2012).…”
Section: Model Results and Their Validationmentioning
confidence: 99%
“…Factors such as the existence of internally mixed aerosols (e.g., Jacobson, 2001), non-spherical particles (e.g., Wang et al, 2013) or the presence of upper aerosol layers or residual layers (e.g., Seguel et al, 2013) might help explain model underestimation with respect to observations. The study by Seguel et al (2013) showed near surface ozone origin measured in the residual layer by ozonesondes that accumulates between the top of the mixed layer and the base of the subsidence inversion. Additionally, data from an elastic Light Detection and Ranging system, and a ceilometer over Santiago show unequivocal layers of aerosols above the mixed boundary layer (Muñoz and Alcafuz, 2012).…”
Section: Model Results and Their Validationmentioning
confidence: 99%
“…During winter, it is visually evident that black carbon and dust particles associated with traffic deposit over the snow in the ski resort of Portillo, on the Chilean side. During summertime, Seguel et al (2013) indicate that regional transport of polluted air from the lowlands is likely to occur up to the Aconcagua valley. The measurements in our field campaign, to test the hypothesis that the pollution from Santiago could reach high altitudes during winter, were made up at a different valley (not the one with the busy highway), in order to avoid the clear influence of the vehicles that emit particles high up in the Andes.…”
Section: Discussionmentioning
confidence: 99%
“…Air masses following these trajectories would not be directly in contact with the polluted central Santiago region. In fact, they would be in contact with pollutants characteristics of the southern periphery of Santiago, where other studies have indicated (Seguel et al, 2013;Gramsch et al, 2014) that the air quality is not correlated with conditions in Santiago and sometimes even considered more representative of background aerosol concentrations. A detailed analysis of the individual trajectories in this cluster indicates arrival at the research site mainly between 1800 LT and 0300 LT. Recall that CN concentrations reached a maximum at the research site at 18:00 LT (Fig.…”
Section: Mesoscale Circulationsmentioning
confidence: 99%
“…These processes are seldom monitored on a regular basis, and so far, few field measurement campaigns have been carried out [e.g., Seguel et al, 2013].…”
Section: Measurements Of Air Quality In Cities and Transport To The Amentioning
confidence: 99%
“…Assessing the impacts of air pollution in the mountains downwind from cities and rural areas will require characterization of the vertical distribution of gases and aerosols, which depend on boundary layer processes and mesoscale circulations. These processes are seldom monitored on a regular basis, and so far, few field measurement campaigns have been carried out [e.g., Seguel et al, 2013].…”
Section: Measurements Of Air Quality In Cities and Transport To The Amentioning
confidence: 99%